Training of Physical Education Teachers in the Context of Digital Education Implementation - Petrovich Olesov, Nikolay (2020)
In the context of digital education implementation, addressing the problem pertaining to the training of highly qualified physical education (PE) teachers in the Republic of Sakha (Yakutia) is essential for the innovative development of the region, along with that of its scientific and educational environments. To this end, specialists should improve their professional skills in order to develop and effectively use advanced educational technologies that take into account the specific conditions of work, study, life as well as the national and cultural traditions of the region. The current article highlights that the implementation of digital education requires complex transformations in the systems of both pedagogical and physical education, which are influenced by progressive digital and information technologies. However, its practical implementation requires a change in the goals, along with the organizational forms and technologies of educational activities, based on information and communication technology (ICT) and network technologies, in addition to the development of productive strategies to integrate innovations into the traditional educational process. Thus, the aim of this study is to substantiate the current trends regarding the development of digital education and training of PE teachers in the Republic of Sakha (Yakutia), by means of the analyses of foreign and domestic researchers’ experiences. Further, its theoretical aspect delves into the analysis of the research conducted on digital education and, primarily, the ways in which it can be implemented in the educational process of the Institute of Sport and Physical Education (ISPE), Ammosov North-Eastern Federal University (NEFU). On the other hand, the practical section of this study presents a comparison between the knowledge of part-time and full-time students studying at the ISPE, NEFU, concerning the framework of digital educational materials’ implementation for the training of future PE teachers. The results showed the considerable improvement of the students’ knowledge on the importance of ICT and digital resources, in addition to an increased level of digital competence regarding professional activity.